2012
DOI: 10.1111/j.1096-3642.2012.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Revised systematics of Palaeozoic ‘horseshoe crabs’ and the myth of monophyletic Xiphosura

Abstract: The monophyly of the class Xiphosura is critically re-examined. For the first time a phylogenetic analysis of a number of synziphosurine and xiphosurid taxa is performed together with representatives of the other chelicerate orders also included as ingroup taxa. Xiphosura as currently defined is shown to be paraphyletic, and a revised classification is presented. Previous characteristics used to unite the xiphosurids (possessing a fused thoracetron) and a paraphyletic grade of synziphosurines (retaining freely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 107 publications
(166 reference statements)
4
127
0
Order By: Relevance
“…There are also fossils like Weinbergina opitzi Richter and Richter, 1929 which also appear to have an 'extra' pair of prosomal legs. This species was originally interpreted as a horseshoe crab, but is now considered to be at a more basal grade of organisation (Lamsdell, 2013). In a similar vein we should note the embryological observations of Scholl (1977) on modern horseshoe crabs e confirmed morphologically by Shultz (2001) e which showed that in this group some opisthosomal segments are incorporated into the prosomal head shield.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are also fossils like Weinbergina opitzi Richter and Richter, 1929 which also appear to have an 'extra' pair of prosomal legs. This species was originally interpreted as a horseshoe crab, but is now considered to be at a more basal grade of organisation (Lamsdell, 2013). In a similar vein we should note the embryological observations of Scholl (1977) on modern horseshoe crabs e confirmed morphologically by Shultz (2001) e which showed that in this group some opisthosomal segments are incorporated into the prosomal head shield.…”
Section: Introductionmentioning
confidence: 89%
“…Briggs and Collins, 1988;Orr et al, 2000;Chen et al, 2004) have been proposed either as taxa belonging to the chelicerate stem-lineage or as early branches within the chelicerates. Indeed Lamsdell (2013) proposed that some fossils traditionally assigned to horseshoe crabs may in fact belong to the stem-lineage of other chelicerate clades (see 3.4). Chelicerates can be united by the synapomorphy of the first pair of head appendages being modified into chelate or clasp-knife structures usually referred to as the chelicerae or chelifores.…”
Section: Introductionmentioning
confidence: 99%
“…Xiphosura (comprising Xiphosurida and its stem lineage sensu Lamsdell (2013)) in general, and limulids in particular, are considered to have a relatively poor fossil record, largely due to their unmineralized exoskeleton and predilection for marginal environments that are not well represented in the stratigraphic record (Babcock et al 2000). A number of fossil taxa have, however, been assigned to modern genera, Limulus in particular (Zinken 1862;Watson 1909;Reeside and Harris 1952); of the thirteen currently valid fossil limulids, five are allied with Limulus or Tachypleus, although the majority of these allocations rely only on gross similarity.…”
Section: Introductionmentioning
confidence: 99%
“…The Atlantic horseshoe crab, Limulus polyphemus (Linnaeus, 1758), is the best documented extant xiphosurid, and has been the subject of detailed anatomical (Owen, 1872;Lankester, 1881;Shultz, 2001;Battelle, 2006;Bicknell et al, 2018a), biochemical (Kaplan et al, 1977), physiological (Sokoloff, 1978) and population dynamic (e.g., Botton, 1984;Brockmann, 1990;Schaller et al, 2005;Gerhart, 2007) investigations since the 1800s (van der Hoeven, 1838; Walls et al, 2002). Palaeontologists have studied xiphosurids for multiple reasons, including a fossil record that extends as far back as the lower Ordovician, 480 million years ago Van Roy et al, 2010;Briggs et al, 2012;Lamsdell, 2013;Bicknell et al, 2018a, b). Furthermore, paleontologists have been intrigued by the morphological similarities of L. polyphemus and fossil xiphosurids like Yunnanolimulus luopingensis Zhang et al, 2009 (Guanling Formation, China, Triassic;Hu et al, 2017), Mesolimulus walchi (Desmarest, 1822) (Solnhofen Limestone, Germany, Jurassic; Sekiguchi and Sugita, 1980;Smith and Berkson, 2005) and Limulus darwini Kin and Błaże-jowski, 2014 (Sławno Limestone, Kcynia Formation, Poland, Late Jurassic;Błażejowski, 2015).…”
Section: Introductionmentioning
confidence: 99%